2008
DOI: 10.1021/bi8001055
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Covalent Adduct Formed between Mycobacterium tuberculosis β-Lactamase and Clavulanate

Abstract: The intrinsic resistance of Mycobacterium tuberculosis to the beta-lactam class of antibiotics arises from a chromosomally encoded, extended spectrum, class A beta-lactamase, BlaC. Herein, we report the X-ray crystallographic structure of BlaC inhibited with clavulanate at a resolution of 1.7 A with an R-factor value of 0.180 and R-free value of 0.212 for the m/ z +154 clavulanate-derived fragment observed in the active site. Structural evidence reveals the presence of hydrogen bonds to the C1 carbonyl along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 26 publications
(37 reference statements)
5
66
1
1
Order By: Relevance
“…To stabilize the adduct of Ldt Mt2 and carbapenem (or any other potential inhibitor of Ldt Mt2 ), tautomerization is necessary but not sufficient, and the conformational change in the second step likely also plays an important role. The results reported here, together with the reported structure of the BlaC-meropenem complex [15], reveal the structural basis for the stabilization of enzymecarbapenem adducts and may suggest new strategies for the design of antibiotics derived from β-lactams to fight against XDR M. tuberculosis.…”
Section: Dear Editormentioning
confidence: 58%
“…To stabilize the adduct of Ldt Mt2 and carbapenem (or any other potential inhibitor of Ldt Mt2 ), tautomerization is necessary but not sufficient, and the conformational change in the second step likely also plays an important role. The results reported here, together with the reported structure of the BlaC-meropenem complex [15], reveal the structural basis for the stabilization of enzymecarbapenem adducts and may suggest new strategies for the design of antibiotics derived from β-lactams to fight against XDR M. tuberculosis.…”
Section: Dear Editormentioning
confidence: 58%
“…As mycobacterial susceptibility to lactams is quite high in the absence of lactamase activity , Quinting et al, 1997, effective chemical inactivation of lactamases should similarly increase lactam sensitivity in these bacteria. In fact, in vitro studies first showed that three FDA-approved inhibitors, sulbactam, tazobactam, and clavulanate, effectively inhibit nitrocefin degradation by purified BlaC protein (Hugonnet & Blanchard, 2007, Tremblay et al, 2008. While sulbactam inhibits BlaC competitively and reversibly, tazobactam inhibits BlaC in a time-dependent manner with reappearing enzyme activity.…”
Section: Potentiation Of Lactams In Mycobacteriamentioning
confidence: 99%
“…While sulbactam inhibits BlaC competitively and reversibly, tazobactam inhibits BlaC in a time-dependent manner with reappearing enzyme activity. Interestingly, clavulanate forms hydrolytically stable, inactive forms of the enzyme, completely and irreversibly inhibiting BlaC in a mechanism in which after acylation of clavulanate, a secondary ring-opening leads to reactive intermediates that occupy the active site of the enzyme (Figure 2 B) (Hugonnet and Blanchard 2007;Tremblay et al 2008). Hence, clavulanate provides a potential lead for the development of effective lactam potentiators for TB.…”
Section: Potentiation Of Lactams In Mycobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Cette étude a montré d'une part que BlaC hydrolysait de façon peu efficace les β-lactamines de la famille des carbapénèmes (imipénème et méropénème), mais surtout qu'il existait déjà sur le marché un puissant inhibiteur de l'enzyme : l'acide clavulanique. Parmi les inhibiteurs classiques de β-lactamases (tazobactam, sulbactam et acide clavulanique), seul l'acide clavulanique inhibe l'enzyme de façon irréversible, grâce à un réarrangement de la molécule au niveau de son site actif observé par l'analyse de la structure cristallographique de la protéine [7]. L'inhibition de l'enzyme par l'acide clavulanique pourrait donc permettre de restaurer l'activité des β-lactamines.…”
unclassified